Internalization of Religious Moderation in Islamic Boarding Schools - Mulia Nasution; Hasan Bakti Nasution; Asnil Aidah Ritonga (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Indonesia has a high level of diversity that can serve as both a strength and a source of conflict if it is not managed through the values of religious moderation. Islamic boarding schools (pesantren), as Islamic educational institutions, play a strategic role in instilling these values, although the process of internalization still faces conceptual, pedagogical, and social challenges. This study aims to analyze the process of internalizing religious moderation in Islamic boarding schools in Padangsidimpuan City, including its forms of internalization, supporting and inhibiting factors, and its implications for students’ attitudes. The research employs a qualitative approach with a multi-site case study design at Al-Ansor Manunggang Julu Islamic Boarding School and Darul Istiqomah Huta Padang Islamic Boarding School. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using an inductive-interactive technique. The findings show that internalization occurs through formal learning, habituation within the pesantren environment, and the exemplary role of the kiai. Supporting factors include pesantren culture, scholarly traditions, and external support, while the main obstacles are limited educator competence and the influence of digital media. This process shapes students’ attitudes to be more open, tolerant, and dialogical, with important implications for strengthening exemplary leadership and digital literacy.